Algorithms for planning working time under interval uncertainty - Yu. N. Sotskov; N. G. Egorova; N. M. Matsveichuk (Informatika)
Time-management refers to planning the available time in correspondence with personal goals and preferences of the employee. The criterion for efficient time-management lies in achieving definite goals in minimum possible time. This paper presents a short review of the literature on time-management. It is shown how scheduling theory may be used for optimal planning in time-management. The problem of minimizing the total (average) weighted completion time of the planned jobs by an employee is considered provided that only lower and upper bounds of the possible processing time of each job are known before scheduling. Software for constructing a permutation of the given jobs with the largest relative semi-perimeter of the optimality parallelepiped has been developed. Computational experiment on the computer showed the effectiveness of the developed algorithms for constructing schedules for time-management.